Section 2.5 : Quadratic Equations - Part I
16. Use the Square Root Property to solve the equation.
(6t+1)2+3=0Show All Steps Hide All Steps
Start SolutionThere really isn’t too much to this problem. Just recall that we need to get the squared term on one side of the equation by itself with a coefficient of one. For this problem that gives,
(6t+1)2=−3 Show Step 2Using the Square Root Property gives,
6t+1=±√−3=±√3iTo finish this off all we need to do then is solve for t by subtracting 1 from both sides and then dividing by the 6. This gives,
6t=−1±√3it=−1±√3i6=−16±√36iNote that we did a little rewrite after dividing by the 6 to put the answer in a more standard form for complex numbers.
We then have the following two solutions : \require{bbox} \bbox[2pt,border:1px solid black]{{t = - \frac{1}{6} - \frac{{\sqrt 3 }}{6}i\,\,\,{\mbox{and }}t = - \frac{1}{6} + \frac{{\sqrt 3 }}{6}i}}.